Synthesis of Tetrasubstituted Thiophenes via Direct Metalation - Skácel, Jan; Dračínský, Martin; Janeba, Zlatko (The Journal of organic chemistry, 2020)
Thiophene moiety can be derivatized by various synthetic procedures. The most convenient method seems to be derivatization via direct metalation, but synthesis of polysubstituted thiophenes bearing reactive groups is difficult because of high reactivity of organometallic reagents. This work reports the preparation of complex heterocyclic compounds using direct metalation of thiophenes with various reagents (Knochel-Hauser bases, LDA) as an efficient synthetic tool.